Symptoms variation and molecular characterization of Strawberry vein banding virus in Bali, Indonesia - Phabiola, Trisna Agung; Selangga, Dewa Gede Wiryangga; Wirya, Gusti Ngurah Alit Susanta; Sudiarta, I Putu; Dinarkaya, Shah Mahapati; Listihani, Listihani (Universitas Lampung, 2025)
Vein banding disease has affected young strawberry leaves in Bali over the past five years. Caused by Strawberry vein banding virus (SVBV), the disease is primarily associated with fruit size reduction, though its exact impact remains unclear. This study aims to assess symptom variation, disease severity, and the molecular characteristics of SVBV in Bali strawberry plants. Field observations and molecular identification were conducted using PCR with SVBV-specific primers targeting the CP gene. Samples were collected from ten locations in Bali, including Pancasari, Candikuning, Wanagiri, Gobleg, and Kembang Merta. SVBV DNA from Candikuning, Pancasari, and Kembang Merta was successfully amplified, confirming SVBV infection as the cause of vein banding symptoms. SVBV induces vein banding with upward and downward leaf curling. Disease incidence was highest in Pancasari 1 and 3 (80%) and lowest in Wanagiri 1 and Gobleg (20–28%). Disease severity ranged from 13% to 83%, with the highest recorded in Pancasari, Buleleng, and the lowest in Kembang Merta, Tabanan. Molecular analysis revealed that the SVBV isolate from Bali shares 99.3–100% sequence homology with Chilean isolates. Phylogenetic analysis showed clustering with SVBV isolates from the United States, Brazil, and Chile. This study provides the first molecular characterization of SVBV in Bali, contributing to a better understanding of its epidemiology and potential impact on strawberry production.